The enhancing effects of testosterone in exposure treatment for social anxiety disorder: a randomized proof-of-concept trial - Hutschemaekers, Moniek H. M.; de Kleine, Rianne A.; Hendriks, Gert-Jan; Kampman, Mirjam; Roelofs, Karin (Translational psychiatry, 2021)
Individuals with a social anxiety disorder (SAD) show hypofunctioning of the hypothalamus–pituitary-gonadal (HPG) axis, which is linked to social fear and avoidance behavior. As testosterone administration has been shown to facilitate social-approach behavior in this population, it may enhance the effectiveness of exposure treatment. In this proof-of-concept study, we performed a randomized clinical assay in which 55 women diagnosed with SAD received two exposure therapy sessions. Session 1 was supplemented with either testosterone (0.50 mg) or placebo. Next, transfer effects of testosterone augmentation on within-session subjective fear responses and SAD symptom severity were assessed during a second, unenhanced exposure session (session 2) and at a 1-month follow-up, respectively. The participants having received testosterone showed a more reactive fear pattern, with higher peaks and steeper reductions in fear levels in session 2. Post-hoc exploration of moderating effects of endogenous testosterone levels, revealed that this pattern was specific for women with high basal testosterone, both in the augmented and in the transfer session. In contrast, the participants with low endogenous testosterone showed reduced peak fear levels throughout session 1, again with transfer to the unenhanced session. Testosterone did not significantly affect self-reported anxiety. The effects of testosterone supplementation on fear levels show transfer to non-enhanced exposure, with effects being modulated by endogenous testosterone. These first preliminary results indicate that testosterone may act on important fear mechanisms during exposure, providing the empirical groundwork for further exploration of multi-session testosterone-enhanced exposure treatment for SAD.